Kajian Pendidikan Islam Di Sulawesi Selatan Dalam Perspektif Historis dan Sosial - Fajar Anugrah; Fitri Ramadani; Idrus L (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines Islamic education in South Sulawesi through a historical and sociological perspective using a qualitative library research approach. The analysis integrates historiographical and sociological frameworks to reconstruct the development of Islamic educational institutions and interpret their social implications. Findings indicate that Islamic education evolved from early informal and community-based learning systems into structured institutional forms, reflecting adaptive responses to socio-cultural and intellectual transformations. The study reveals that Islamic education has functioned not only as a medium of religious knowledge transmission but also as a mechanism for shaping social norms, collective identity, and moral values. Furthermore, contemporary developments demonstrate an epistemological shift toward integrative and inclusive educational models that reconcile religious and scientific knowledge. These models emphasize character formation, multicultural awareness, and moderation, positioning Islamic education as a dynamic agent of social change. The research contributes to the academic discourse by offering a comprehensive understanding of the interconnected historical trajectories and social functions of Islamic education in a localized Indonesian context. It highlights the significance of adaptive educational paradigms in sustaining relevance within rapidly changing global environments.